PENGARUH TERAPI BEKAM BASAH TERHADAP TEKANAN DARAH PADA PASIEN DENGAN HIPERTENSI GRADE I DI RUMAH SEHAT MINA - Mega Ayudia Saundari; Siti Rahmalia Hairani Damanik; Jumaini Jumaini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
The case of hypertension keeps increasing as the population increases. Long lasting hypertension can cause permanent damage to vital organs such as heart, kidney and brain. Management of hypertension can be non-pharmacology, one of which is wet cupping therapy. This study aims to determine the effect of wet cupping therapy on blood pressure in patients with grade 1 hypertension at Rumah Sehat Mina with pre-experiment research design and one group pretest-postest design without control group. The sample was 24 respondents based on the inclusion criteria. The sample selection used nonprobability sampling technique with accidental sampling method. Data collection tools used are observation and interview sheets, manual sphygmomanometer, stethoscope and cupping equipment. Data analysis method used univariate analysis to know the distribution of respondent and bivariate characteristic using wilcoxon test. The results showed the characteristics of respondents were 40-60 years old (66.7%), with the most female sex (62.5%), the majority of high school educated (50.0%) and not working (37.5%). The result of statistical test found that there is a change of blood pressure, decreasing with difference of mean value of systole (4,67) and diastol (1,79). The statistical test showed the effect of wet cupping therapy on systolic blood pressure in patients with grade 1 hypertension with p value (0.003) <α (0.05), and there was no effect of wet cupping therapy on diastolic blood pressure in patients with grade 1 hypertension with p value (0.108)> α (0.005).Keywords: Blood Pressure, Hypertension, Wet Cupping Therapy